Phylogeny Trumps Chemotaxonomy: A Case Study Involving Turicella otitidis - Baek, Inwoo; Kim, Mincheol; Lee, Imchang; Na, Seong-In; Goodfellow, Michael; Chun, Jongsik (Frontiers in Microbiology, 2018)
The genus Turicella was proposed to harbor clinical strains isolated from middle-ear fluids of patients with otitis media. 16S rRNA phylogeny showed that it belonged to the mycolic- acid-containing actinobacteria, currently classified in the order Corynebacteriales, and was closely related to the genus Corynebacterium. A new genus was proposed for the organisms as unlike corynebacteria they lacked mycolic acids and had different menaquinones. Here, we carried out large-scale comparative genomics on representative strains of the genera Corynebacterium and Turicella to check if this chemotaxonomic classification is justified. Three genes that are known to play an essential role in mycolic acid biosynthesis were absent in Turicella and two other mycolate-less Corynebacterium spp., explaining the lack of mycolic acids resulted from the deletion of genes and does not confer any phylogenetic context. Polyphasic phylogenetic analyses using 16S rRNA, bacterial core genes and genes responsible for synthesizing menaquinones unequivocally indicate that Turicella is a true member of the genus Corynebacterium. Here, we demonstrate that menaquinone and mycolic acid that have been used as critical taxonomic markers should be interpreted carefully, particularly when genome-based taxonomy is readily available. Based on the phylogenetic analysis, we propose to reclassify Turicella otitidis as Corynebacterium otitidis comb. nov.